Decent work - safe work: introductory report. XVIIth World Congress on Safety and Health at Work, Orlando, 18-22 Sep. 2005 (Geneva, 2005)
" ... The ILO firmly believes that work-related accidents and ill-health can and indeed must be prevented, and that action is needed at international, regional, national and enterprise levels to achieve this. Yet, globally, the statistics appear to show an increasing trend in occupational accidents and diseases. As the ILO Director-General said when referring to the Decent Work Agenda, “Decent Work must be Safe Work, and we are a long way from achieving that goal”. The protection of workers against injury and disease has always been a key issue forthe ILO since it was founded in 1919, and many of its activities have been directed to that end. Many Conventions, Recommendations and other instruments on occupational safety and health (OSH) have been adopted over the years, and these have helped to improve working conditions throughout the world. This impetus has been maintained, and recent years have seen both theadoption of a Global Strategy for OSH, which seeks to integrate and enhance the ILO’s activities in this area, and the development of a new promotional framework for OSH, intended for adoption as a Convention in 2006. This report provides an overview of the most recent estimates of occupational and work-related accidents and diseases, world-wide, some of the causes for recent changes and what the ILO and its member States are doing to improve conditions in the workplace for the millions who are at risk from injury. ..." (From the introduction)